Nailbiter. Volume seven, Nailbiter returns - Williamson, Joshua; Williamson, Joshua; Henderson, Mike, 1981- (Nailbiter ;)
Is the Nailbiter alive? Where is Sheriff Crane? Are they part of the serial killer copycats' horrific game of death?! The only person who can answer all these questions is the Nailbiter's daughter!